2020
DOI: 10.18295/squmj.2020.20.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus Calmette-Guérin (BCG) Vaccine: Is it a better choice for the treatment of viral warts?

Abstract: Objectives: This study aimed to compare the effectiveness of the bacillus Calmette-Guérin (BCG) vaccine with topical salicylic acid (SA) in the treatment of viral warts. Methods: This non-randomised controlled trial was conducted at the Al-Sader Teaching Hospital, Basrah, Iraq, from January 2016 to April 2017. A total of 201 patients with viral warts were injected with an intradermal purified protein derivative. Subsequently, those with negative tuberculin test results received an intradermal BCG vaccination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The possible connection between COVID‐19 vaccine and clinical resolution of viral warts is interesting, as some vaccines (mumps, measles, rubella vaccine; Bacillus Calmette–Guérin vaccine) are already applied intralesionally in the treatment of viral warts. 7 , 8 The studies evaluating cytokine profile in warts treated with this method showed an important role of IL‐10 downregulation and upregulation of IL‐1 and IFN‐γ. 9 Additionally, there have been case reports showing clinical resolution of viral warts after systemic administration of quadrivalent HPV vaccine.…”
Section: Figurementioning
confidence: 99%
“…The possible connection between COVID‐19 vaccine and clinical resolution of viral warts is interesting, as some vaccines (mumps, measles, rubella vaccine; Bacillus Calmette–Guérin vaccine) are already applied intralesionally in the treatment of viral warts. 7 , 8 The studies evaluating cytokine profile in warts treated with this method showed an important role of IL‐10 downregulation and upregulation of IL‐1 and IFN‐γ. 9 Additionally, there have been case reports showing clinical resolution of viral warts after systemic administration of quadrivalent HPV vaccine.…”
Section: Figurementioning
confidence: 99%
“…reported a case of regression of verruca vulgaris after receiving a ChAdOx1‐S COVID‐19 vaccine (AstraZeneca) 17 . Indeed, it has been found that some vaccines (mumps, measles, rubella vaccine BCG) can be used to treat warts vulgaris 18 . Moscato et al.…”
Section: Discussionmentioning
confidence: 99%
“…17 Indeed, it has been found that some vaccines (mumps, measles, rubella vaccine BCG) can be used to treat warts vulgaris. 18 Moscato et al reported verruca vulgaris was cured after vaccination with the quadrivalent HPV vaccine. Studies have found that this may be related to the downregulation of IL-10 and the upregulation of IL-1 and IFN-c levels.…”
Section: Erkayman Et Al Reported a Case Of Multiple Refractory Viral ...mentioning
confidence: 99%
“…By analyzing the above data, it is not difficult to see that children and infants' mortality decreased by approximately 50% after BCG vaccination. BCG's protection can hardly explain this data against TB alone, which may be related to BCG's protection against unrelated infectious agents (including viruses, bacteria, and protozoa) [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] ( Table 1 ). These beneficial effects have been considered to be related to the nonspecific effects, including prophylactic protection effects, immunotherapy effects, as well as enhancement effects on other vaccines.…”
Section: Nonspecific Protection Effects Of Bcgmentioning
confidence: 99%
“… Pathogens or diseases Research subjects Study type Effects of BCG The specific cellular immunity of BCG Ref Yellow fever virus healthy Dutch male subjects ( n = 30) RCT Induced epigenetic reprogramming in human monocytes, functional reprogramming, and protection against non-related viral infections Reduction of viremia was highly correlated with the upregulation of IL-1β [26] Influenza A (H1N1) Healthy volunteers ( n = 40) RCT Resulted in a more pronounced increase and accelerated induction of functional antibody responses against the 2009 pandemic influenza A(H1N1) vaccine strain Enhanced antibody production and more sustained IFN-γ production [27] HSV Patients with genital herpes ( n = 155) RCT Recurrence over 9 months of follow-up was 0.528 recurrences per month compared with 0.392 in placebo recipients NA [28] HPV Children with common and plane warts ( n = 80) Case series Improved clearance of viral warts The activation of CD4 lymphocytes and an increase in IL-1, IL-2, and TNF-α [29] RRP patients ( n = 15) Case-control Improved clearance of viral warts Potentiating Treg differentiation, limiting hyperactivation and virus-specific T cell clones depletion, and restoring a Th1 cytokine background. [30] Patients with warts ( n = 60) RCT Improved clearance of viral warts NA [31] Patients with warts ( n = 190) Non-randomized controlled trial More effective than topical salicylic acid for treating viral warts NA [32] RSV Infants ( n = 386) Case-control A beneficial effect of BCG vaccination for girls NA [33] AURTI Patients with AURTI ( n = ...…”
Section: Nonspecific Protection Effects Of Bcgmentioning
confidence: 99%